If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7m + 7n = 0 Solving 7m + 7n = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-7n' to each side of the equation. 7m + 7n + -7n = 0 + -7n Combine like terms: 7n + -7n = 0 7m + 0 = 0 + -7n 7m = 0 + -7n Remove the zero: 7m = -7n Divide each side by '7'. m = -1n Simplifying m = -1n
| 2x+4x+3y= | | 79-4x=23x+19 | | (n-5)*7=35 | | (n-6)*4=40 | | -171x-9x=10x+19 | | 3x+x/2=15 | | 3a-4=0 | | 8x+3=x+38 | | x*2=8 | | 4x*5x=20 | | 4x+3x=12 | | 4x+5x=200 | | 4x+5x=10 | | 4x+5x=100 | | 4yx+5x=20 | | 4x+5y=5y | | b-8=10 | | 5x+4y=31 | | a-8=4 | | 2y-15+3y+3=24 | | z-5=r | | a+9=16 | | 2s+4t-2s-3t= | | 8z=-104 | | 5x=-65 | | 74-6x=12x+18 | | 13-9x=57-23x | | 83-3x=24x+17 | | 5-10x=170-45x | | 62-6x=8x-4x | | 132-5x=4x+24 | | -17-6x=7-10x |